Compartilhamento de informações na Universidade Federal de Minas Gerais: um estudo de caso no Centro de Apoio à Educação a Distância - Maria das Graças Moreira (2019)
The purpose of this study was to investigate how information sharing occurs within the team of the Center for Support to Distance Education of the Federal University of Minas Gerais (CAED/UFMG). The most commonly usedmethods of sharing information by the team as well as the reasons for sharing information in the daily working life of the team were identified. The sample consisted of 40 CAED employees. Quantitative and qualitative approaches were used. Data collection was based on bibliographical research and field research. The experimental design of the study was exploratory and descriptive. The instruments to collect field data were a questionnaire and a semi-structured interview. Statistical techniques were used to tabulate the quantitative results that resulted in graphs and tables demonstrating the data obtained with the responses to the questionnaire. For the interpretation of the interviews, content analysis was used with grouping of the most relevant informationextracted from them. The CAED/UFMG team has been using e-mail, smartphones, fixed telephony, Instagram, WhatsApp, formal meetings, congresses, seminars and colloquia as the main methods of sharing information. In the opinion of the respondents, information sharingpractices contribute to team growth and innovation in the development of the activities of the sector, and help solving problems, improving the knowledge acquired, bringing team members closer together and strengthening trust among employees. The fundamental reasons for the team to exchange experiences are related to the aid in the implementation of daily tasks, the possibility of exchanging experiences with people from different fields of activity and the cooperationof knowledge for individual and organizational development. The inadequate physical structure of the work environment and the limited autonomy of action were identified as obstacles to sharing information. In view of this, it is suggested that the sector coordinators should encourage employees to use the intranet as a way to implement an organizational culture that enhances the sharing of information and actions of interest to the team; identify, among the employees, those with a leadership profile to increase motivation; think on how to improve the exchange of information by supervising the team through meetings and informal dialogues, consolidating the culture of sharing in the work environment; and make efforts with the team and the central administration to restructure thephysical environment, reallocating the sectors with correlated activities, taking advantage of the physical space and, mainly, reducing the time spent in the accomplishment of the daily tasks. It is necessary that periodic meetings be promoted as a means of obtaining feedback from the team regarding the objectives outlined and the results achieved.